Is it morally wrong to engage in violent sexual kinks and fetishes? - Mansul, Misyal Sonnia (Nanyang Technological University, 2025)
In recent years, BDSM (Bondage and Discipline, Dominance and Submission, Sadism and Masochism), has raised moral concerns regarding informed consent in violent sexual practices. This paper explores the moral permissibility of engaging these kinks, particularly when the line between consensual and non-consensual harm is unclear. With that understanding, I argue that such practices are morally permissible insofar as informed consent is present and that in there being a mutual understanding between the parties involved, the harm incurred leads to a net overall benefit. In the first half, I outline Kant’s view on objectification and Martha Nussbaum’s defense of sexual objectification, arguing that certain forms of objectification can be morally permissible. Next, I address the problematic nature of inflicting harm, which is often assumed as undesirable. In the second half of the paper, I defend my position by explicating the benefits of harm and how the consensual nature of these acts does not strip individuals of their autonomy. Lastly, I reference L.A Paul’s theory of transformative experience to illustrate that, despite the epistemic limitations posed by transformative experiences i.e. BDSM acts, their informed consent still holds. Consequently, I conclude that these acts are morally permissible insofar as it is understood within the broader context of autonomy and ethical sexual practices.